CLINICAL CHARACTERISTICS AND FACTORS ASSOCIATED WITH DYSMENORRHEA SEVERITY AMONG FEMALE STUDENTS AT THE UNIVERSITY OF MEDICINE AND PHARMACY, VIETNAM NATIONAL UNIVERSITY, HANOI IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical characteristics of dysmenorrhea and investigate selected factors associated with the severity of dysmenorrhea among female students at the University of Medicine and Pharmacy, Vietnam National University, Hanoi in 2025.Subjects and methods: A descriptive cross-sectional study was conducted among 172 female students who were currently enrolled at the University of Medicine and Pharmacy, Vietnam National University, Hanoi and reported experiencing menstrual pain. Data were collected using a structured self-administered questionnaire and analyzed with appropriate statistical tests.Results: The mean age of participants was 21.6 ± 1.8 years. Most students reported regular menstrual cycles and a duration of menstruation within the normal range. Dysmenorrhea was predominantly mild to moderate in severity, with a mean visual analog scale score of 3.5 ± 2.0; however, 7.0% of participants reported severe pain. A total of 33.1% of students reported absence from classes during menstruation. In univariate analysis, stress level, history of pregnancy and childbirth, family history of dysmenorrhea, history of gynecological diseases, and smoking status were significantly associated with the severity of dysmenorrhea (p < 0.05).Conclusion: Dysmenorrhea is a common condition among female students and has a considerable impact on academic activities. In univariate analysis, stress level, family history of dysmenorrhea, history of gynecological disease, history of pregnancy and childbirth, and smoking were associated with pain severity. These factors should be taken into account in counseling, monitoring, and reproductive health support programs for students.
Keywords: dysmenorrhea; pain severity; female students; menstrual pain.